0335 Polysomnography in Insomnia Disorder. (12th April 2019) - Verkler, Jelena; Koshorek, Gail; Roth, Thomas; Roehrs, Timothy
Abstract: Introduction: A recent meta-analysis compared polysomnograms (PSGs) of people with insomnia to healthy controls; results showed short sleep time and reduced slow-wave and REM sleep in insomnia. Among people with insomnia, studies have shown morbidity associated with insomnia is found primarily in people with PSG short sleep. Here we characterize the distribution and nature of PSG sleep among people diagnosed with DSM-V insomnia disorder. Methods: Insomnia disorder (DSM-V) subjects, aged 23-61 yrs, (n=67, 63 females), absent other sleep disorders, unstable medical or psychiatric disorders or drug dependency volunteered for a clinical trial. The final enrollment step involved collection of a standard 8-hr PSG evaluating sleep disturbance among trial participants. PSGs were scored following ASSM criteria, by reliable scorers, for sleep efficiency (SE), latency to persistent sleep (LPS), wake after sleep onset (WASO) and percent sleep stages (N1, N2 N3, and NR). Results: There was wide variation in SE ranging from 40-97% with a mean of 82% and a median of 84% (6.5 hrs sleep). The SE distribution was divided into quartiles (worst - best; Q1: ≤ 76.8%; Q2: 77>84.2%; Q3: 84.3% >90.7%; Q4: ≥ 91%). As might be expected, LPS (F=9.82, p<.001) and WASO (F=38.12, p<.001) similarly improved across the SE quartiles with parallel declines in LPS and WASO over the quartiles. N1% declined (F=6.96, p<.001) and both N3% (F=4.78, p<.001), corrected for age, and NR% increased (F=5.12, p<.001) over quartiles. In post hoc pairwise comparisons between quartiles, SEs of < 77% were associated with reduced N3% and NR% and increased N1% (p<.05) relative to efficiencies of >84%. Conclusion: People meeting DSM-V diagnostic criteria for insomnia disorder display a broad range of PSG-defined sleep disturbance with 50% having SE of less than 84%. SE of <77% (6.2 hrs) is associated with reduced N3% and NR% and increased N1%. Support (If Any): NIDA, grant#: R01DA038177 awarded to Dr. Roehrs